Emprego da biblioteca DrWatson.jl em simulações de ciências térmicas - Portugal, Alessandro Cappellini (2023)
This work, classified as qualitative, proposes to explore and study the potential of the functio nalities available in the DrWatson.jl library that provide engineers and researchers a little concern in relation to the management of their simulations with variation of input parameters, allowing them to focus in the science. The package’s functionality is tested in a simplified Otto Cycle simulation that is close enough to a real cycle, to extract as much as possible what the package has to offer. Such as starting organized projects, creating and activating a virtual environment, commands that facilitate the storage of project data in local directories and their subsequent access, beside to providing assistance to others who want to make independent verifications of simulation results.